Distribution and Dynamics of Radiatively Active Gas (RAG) Emissions From Major Estuaries of the Sundarbans Mangrove, India - Acharya, Avanti; Sanyal, Prasun; Paul, Madhusudan; Gupta, Vandana Kumari; Bakshi, Sneha; Mukhopadhyay, Sandip Kumar (Frontiers in Earth Science, 2022)
The world's largest mangroves ecosystem, the Sundarbans being highly productive and a place for extensive organic matter cycling is considered to be the hotspot for biogeochemical studies in the tropical estuarine environment. Hence, the spatial and temporal dynamics of the biogenic gases (CO2, CH4, and N2O), also known as radiatively active gases (RAG) were measured in mangrove-dominated estuaries of the system. In addition to spatial and seasonal observation, three full tidal cycles were observed at one site. Results showed that the air/water gas saturations were widely distributed and highly variable along the stretch. The gas saturations showed varying responses to salinity and tidal fluctuations. This indicated localised biogeochemical processes may be more influential than simple mixing and dilution processes in controlling the variability of these gases. The surface waters were always supersaturated with CH4 (Up to 13,133%) relative to the atmosphere. However, N2O ranged from 8 to 1286% and CO2 from 30% to 2075%. N2O fluxes were ~4.8 times higher in the pre-monsoon than the post-monsoon. CH4 fluxes were ~3.6 times higher in the pre-monsoon than both the monsoon and the post-monsoon. CO2 fluxes were ~10 times higher in the monsoon than both the pre-monsoon and the post-monsoon. The seasonality in the gas saturation could be linked more to the availability of substrates than physicochemical parameters. Overall, air/water CH4 fluxes varied maximal (0.4 to 18.4 µmol m-2 d-1) followed by CO2 fluxes (-0.6 to 10.9 mmol m-2 d-1), and N2O fluxes varied the least of all (-0.6 to 5.4 µmol m-2 d-1). Interestingly, CH4 and N2O fluxes were positively correlated to each other (p<0.05) suggesting organic matter decomposition as the key factor in the production of these two gases. Finally, these water – air CO2, CH4, and N2O flux estimates show that the estuaries are a modest source of CH4 but fluctuate between sources and sinks for CO2 and N2O gases.